Influence of parties on legislative policy, overseeing criminalization in Iranian law - Kazemi, Seyyed Sajjad (International e-journal of criminal sciences, 2022)
The influence of the political structure of each country on the legislative policy governing criminalization is considered to be a fundamental issue, which requires a theoretical model to be proposed; the degree of intervention of political parties in different countries varies according to democracy, government structure, the influence of individuals and political strata in the government of that country. In the meantime, the extent and quality of the intervention of these parties in criminalization and related issues deserve to be discussed. This role has different procedures such as disciplined and undisciplined performance of members in parties. About whether this role is useful or not, it will be useful if it does not lead to inter-party conflict. The aim is to show political criminalization (street criminalization). In this research, the subject of the research has been studied by descriptive-analytical method and using the tools of collecting and analyzing library resources and applying interdisciplinary knowledge.